Snake in Buddhist & Hindu arts - Zekrgoo, Amir Hossein (Iran Academy of the Arts, 2013)
The book is the 2nd volume of a series under compilation. Each volume is devoted to a certain symbol (animal, plant, human, gestures and postures, tools, etc) within the religious traditions of the East. The present volume is complemented with some 39 images (including 30 color plates and 9 line drawings) and a glossary of technical terms.